Georgia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for Waiver of Performance Criteria, and Request for Rephasing of Disbursements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper focuses on Georgia's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), a Request for Waiver of Performance Criteria, and a Request for Rephasing of Disbursements. The IMF staff considers that recent strong macroeconomic performance in a difficult external environment and efforts to reestablish the momentum of key structural reforms warrant completion of the second review. The IMF staff supports authorities' request for waivers of performance criteria and their request for higher disbursements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet